2023
DOI: 10.1186/s12967-023-04094-7
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomics in ovarian cancer identify a metastasis-associated cell cluster overexpressed RAB13

Abstract: Background Metastasis, the leading cause of cancer-related death in patients diagnosed with ovarian cancer (OC), is a complex process that involves multiple biological effects. With the continuous development of sequencing technology, single-cell sequence has emerged as a promising strategy to understand the pathogenesis of ovarian cancer. Methods Through integrating 10 × single-cell data from 12 samples, we developed a single-cell map of primary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…To better investigate the roles of E0 in epithelial cells, inferCNV showed that E0 displayed the highest gene CNV among all epithelial subgroups, further supported by pseudotime trajectory analysis, positioning E0 at the late stage of tumour cell differentiation with E4 as the starting point (Figure 2 F, G). Along trajectory, late stage of epithelial subclusters indicate tumour cells' metastatic, treatment resistant characteristics 17 .…”
Section: Resultsmentioning
confidence: 99%
“…To better investigate the roles of E0 in epithelial cells, inferCNV showed that E0 displayed the highest gene CNV among all epithelial subgroups, further supported by pseudotime trajectory analysis, positioning E0 at the late stage of tumour cell differentiation with E4 as the starting point (Figure 2 F, G). Along trajectory, late stage of epithelial subclusters indicate tumour cells' metastatic, treatment resistant characteristics 17 .…”
Section: Resultsmentioning
confidence: 99%
“…DEGs between UTUC and BLCA-derived M1 macrophages identified 281 upregulated DEGs and 298 downregulated DEGs. Upregulated DEGs included chemokines (CXCL16, CCL2, CCL3, CCL4L2, and CCL4) and cytoskeleton-associated genes (ACTB, TUBB, DYNLL1, RACK1, and PFN1) ( Supplementary Figure 2E ) ( 50 , 51 ), highlighting distinct immune modulatory and migratory capabilities between these two diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Although many studies have explored the mechanisms and treatment of ovarian cancer at single cell level, the primary focus was given to the commonalities among multiple patients limited by the sample size and the high inter-tumor heterogeneity of ovarian cancer. Nevertheless, a study by Guo et al successfully constructed a cell atlas containing normal epithelium, primary carcinoma, and metastatic carcinoma by integrating single-cell sequence data from 12 patients (81). In this study, the developmental trajectory of cancer cells during metastasis was characterized using pseudo-time trajectory analysis at various phases, and a cell subcluster with commonality in patients and close association with metastasis was found.…”
Section: Ovarian Cancer At Single-cell Resolutionmentioning
confidence: 98%
“…Nevertheless, a study by Guo et al. successfully constructed a cell atlas containing normal epithelium, primary carcinoma, and metastatic carcinoma by integrating single-cell sequence data from 12 patients ( 81 ). In this study, the developmental trajectory of cancer cells during metastasis was characterized using pseudo-time trajectory analysis at various phases, and a cell subcluster with commonality in patients and close association with metastasis was found.…”
Section: Ovarian Cancer At Single-cell Resolutionmentioning
confidence: 99%